Blood and local eosinophil levels in chronic rhinitis: Observations during seasonal allergen exposure and non-exposure - Xu Xu, MSc; Jingyun Li, MD, PhD; Xu Zhang, MD; Lin Xi, MD; Yunbo Gao, MD; Xian Li, MSc; Yuan Zhang, MD, PhD; Luo Zhang, MD, PhD (World Allergy Organization Journal, 2024)
Background: Allergic rhinitis (AR) is a typical type 2 inflammatory disease and eosinophils play a critical role of cardinal effectors in type 2 inflammation. However, the distribution of eosinophils in patients with different subtypes of rhinitis and the effect of allergen exposure on them remain understudied. The aim of this study was to investigate the characteristics and factors influencing the distribution of systemic and local eosinophils in patients with non-AR (NAR), perennial AR (PAR), and seasonal AR (SAR), as well as the effect of seasonal allergen exposure levels on eosinophils. Methods: This was a population-based, cross-sectional observational study of consecutive chronic rhinitis (CR) outpatients who volunteered to participate in the survey during the spring pollen season and non-pollen season of 2023 in Beijing. All participants underwent serum allergen testing, blood routine examination, and nasal secretion smear cytology, and completed questionnaires mainly involving basic information, history review, and symptom assessment. Spring pollen dispersal concentration were considered. Results: A total of 558 CR patients eligible for enrollment were collected, including 198 NAR, 204 PAR, and 156 SAR patients. PAR had the highest blood eosinophil levels and the most severe overall nasal and ocular symptoms of SAR. Compared with subjects with blood eosinophil counts <0.3 × 109/L, those with ≥0.3 × 109/L had significantly more severe nasal and ocular symptoms and a significantly higher rate of comorbid asthma and allergic conjunctivitis. Blood eosinophil levels were significantly higher in SAR patients during the pollen season compared to the non-pollen season, and pollen concentrations were positively correlated with systemic and local eosinophil levels. Conclusions: Blood eosinophil levels varied in patients with different subtypes of rhinitis. Patients with high blood eosinophil levels had more severe overall nasal and ocular symptoms, and that blood eosinophils levels were significantly higher in patients with asthma or allergic conjunctivitis than patients without comorbidities. There was a positive trend between allergen exposure and systemic and local eosinophil levels. Further longitudinal cohort studies are still needed to better analyze the influence of eosinophil levels on the clinical traits of AR.